Individual Effects of Agenda-Setting - Stevenson, Robert L.; Ahern, Thomas J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
The agenda setting hypothesis of mass media effects, which maintains that the mass media set the agenda of public discussion and determine which items are to be discussed and which ignored, was tested. Agenda was defined as an attribute of individual respondents to be compared with those of various media. In a preliminary study, a group of 59 undergraduates completed a questionnaire ranking the importance of six broad news areas and providing information about media use. In the major study, 421 adults were interviewed in June 1972, and of these, 227 were reinterviewed in October 1972. At both times, respondents were asked to assess the salience of a set of six major issues and to respond concerning their media use; content analysis of media coverage was also performed. Results indicated no transfer of media agenda to personal agendas of media users, people exposed to specific media did not have personal agendas more in line with those of the media than did those persons not exposed to those media, and measures of use of newspapers and television for news and measures of exposure to these media did not correlate with measures of agenda fit. (DF)
ERIC Note: Paper presented at the Annual Meeting of the Association for Education in Journalism (62nd, Houston, Texas, August 5-8, 1979).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication (Thought Transfer); Content Analysis; Information Utilization; Mass Media; Media Research; Newspapers; Political Issues; Television; Television Research; Television Viewing; Agenda Setting -- Media Effects; Speeches/Meeting Papers; Reports, Research